Entre « encadrement » et « débordement » : une approche des enjeux du community management dans le champ de la démocratie locale - Olivier Galibert; Nicolas Peirot (Communiquer)
As organizations’ presence on social networks is becoming almost obligatory, local and regional authorities are converting to the so-called “2.0” web paradigm. These strategies, deployed on Facebook, Twitter or any other social networks require monitoring and management skills that only community management seems to be able to provide. This observation leads us to our issue: how does community management and its range of strategic best practices link to local authorities online presence? Through a corpus composed of web pages putting in evidence the conditions of the institutionalization of the practice (expert, administrative and legal marks), we want to formulate one main hypothesis about the development of community management within local democracy. We want to suggest a reorganization of community management from a marketing to a political instrument; a community management more considered as a tool to frame citizens’ expression than a tool to inform them.